Introduction to voltammetric analysis : theory and practice - Thomas, F. G. (Francis George), 1933-; Henze, Günter. (Collingwood, Vic. : CSIRO Pub., 2001)
Presents the basic concepts and principles in an easy-to-read manner, with practical applications from multiple disciplines.
Introduction -- Techniques -- Stripping analysis -- Practical aspects -- Flow-through techniques -- Applications : inorganic species -- Applications : organic species -- Appendices.
"This text is a translation of the German text Polarographie und Voltammetrie: Grunladen und Analytische Praxis (Springer 2001) by Günter Henze"--Preface.
Includes bibliographical references and index.
Print version record.
Keywords: Voltammetry; Electrochemical analysis; SCIENCE -- Chemistry -- Analytic; Electrochemical analysis; Voltammetry; Electronic books; Electronic books